Comprehensive genotyping for 18 blood group systems using a multiplex ligation‐dependent probe amplification assay shows a high degree of accuracy. Issue 11 (29th August 2013) - Haer‐Wigman, Lonneke; Ji, Yanli; Lodén, Martin; de Haas, Masja; van der Schoot, C. Ellen; Veldhuisen, Barbera
Abstract : Background: In recent years genotyping methods have been implemented in blood banks as alternative to comprehensive serologic typing. We evaluated a newly developed assay for convenient and comprehensive genotyping of blood group alleles based on multiplex ligation‐dependent probe amplification (MLPA) technology. Study Design and Methods: We analyzed 103 random and 150 selected samples to validate the specificity of the blood‐MLPA assay that is able to determine the presence, absence, and copy number of 48 blood group and 112 variant alleles of 18 blood group systems. A total of 4038 serologic typing results, including 52 different antigens, were available for these samples. Results: In 4018 (99.5%) of the 4038 serologic typing results the predicted phenotypes by the blood‐MLPA were in concordance with serologic typing. Twenty discordant results were due to false‐positive serologic results (n = 2), false‐negative serologic results (n = 1), inability of routine serologic typing to detect variant antigens (n = 14), or false‐positive prediction from the blood‐MLPA due to the presence of a null allele (n = 3). Conclusion: The blood‐MLPA reliably predicts the presence or absence of blood group antigens, including almost all clinically relevant blood group antigens, except ABO, in patients and donors. Furthermore, it is the first assay that determines copy numbers of blood group alleles in the same test. It even provides more detailed and accurate information than serologic typing, because most variant alleles are immediately recognized. Since only standard laboratory equipment is needed, this assay finally offers the possibility to comprehensively type recipients and makes extensive matching for selected patients groups more feasible.